Comparative assessment of resistance to enamel demineralization after orthodontic banding with three different cements- An in vitro study. - Ashwith Hegde; Gaurav Gupta; Sonali Khandekar; Tushar Patil; U.s.krishna Nayak (Cumhuriyet University, 2014)
Objectives: This in vitro study was to compare the resistance to enameldemineralization after banding with three orthodontic cements, namely ZincPhosphate (Harvard Cement), ZincPolycarboxylate (Poly-F, Densply) and ResinModified Glass Ionomer Cement [RMGI] (Ortho Band Pak, GC Fuji).Materials and Methods: 80 premolarswere selected which were cleaned, dried and divided into four groups of 20each. Group A was a Control group. Group B, C and D were banded with thestainless steel bands using the respective cements. The teeth were then placedin deionized water for one month. They were debanded, cleaned and placed inartificial demineralizing solution for four weeks. Later they were cleaned andplaced in methylene blue for 24 hours to check the amount of demineralization. Theteeth were cut buccolingually and observed under the Motic Image Digital microscope.For analysis, the depth of dye penetration was measured in µm, which wasconsidered as equal to the depth of demineralization. Results: RMGI cement group showedsignificantly lesser amount of demineralization (6.679 ±3.016µm)  compared to the Zinc Polycarboxylate cementgroup (18.0838± 5.833µm). The Zinc Phosphate cement group(55.360±8.667µm) andthe Control group(76.722± 18.832µm) demonstrated the greatest depth of enameldemineralization. Overall comparison showed a statistically significant difference(F=187.97, p<0.001).Conclusion: RMGI can be safely usedfor banding as it shows greater amount of resistance for enamel demineralization.